Climate Change: Social Risk Perceptions and Mass Media Discourse Configurations in Lithuania - Balžekienė, Aistė; Telešienė, Audronė; Rinkevičius, Leonardas (Sociologija. Mintis ir veiksmas, 2008)
This article aims at analysing public perceptions and mass-media discourse of climate change in Lithuania. Global discourse on climate change stretches from alarmist to sceptical discourses, reaching far behind political and scientific agendas. The empirical evidence, presented in this article, is based upon representative public opinion survey and mass-media monitoring. The results identify, that public discourses on climate change in Lithuania are prevailed by reproducing of knowledge and opinions of foreign sources. That leads to social perceptions of climate change as more threatening to the world in general than to Lithuania in specific. The urgency of climate change problem is situated as least important among other social and economic problems in public consciousness. The debates on climate change in mass media in Lithuania is lacking the critical discussions on climate change causes and effects on the one side, and the issues of social consequences and adaptation to climate change on the other side. Climate change remains as a minor issue of concern both in public perceptions and in mass media discourse.
Keywords: climate change; public risk perceptions; media discourse